Corrections in saccade endpoints scale to the amplitude of target displacements in a double-step paradigm. (12th January 2016) - Kiernan, Dovin; Manson, Gerome; Heath, Matthew; Tremblay, Luc; Welsh, Timothy N.
Highlights: Primary saccade endpoints adapted to target displacements. Magnitude of endpoint adaptations scaled to amplitude of target displacements. Online corrections modify primary saccade trajectories. Abstract: It is widely held that discrete goal-directed eye movements (saccades) are ballistic in nature because their durations are too short to allow for sensory-based online correction. Recent studies, however, have provided evidence that saccadic endpoints can be mediated via online corrections. Specifically, it has been reported that saccade trajectories adapt to the eccentricity of an unexpectedly perturbed target location (i.e., target 'jump' paradigm). If saccades are subject to online correction mechanisms, then the magnitude of such changes should scale to the amplitude of the target jump. To test this hypothesis, saccadic endpoints for trials on which the target jumped one of three amplitudes (Small: 2.5°, Medium: 5.0°, and Large: 7.5°; i.e., Jump trials) immediately after saccade onset were compared with the endpoints of trials in which the target location did not change (i.e., Reference trials). Results showed that primary saccade endpoints for Jump trials were longer than for Reference trials. Importantly, the magnitude of this increase in endpoint scaled with the amplitude of the target jump. Thus, these results support emerging and coalescent evidence that saccade trajectories are subject to online corrections.